The Effect of a Combination of Biodive Fertilizers on The Growth of Sweet Corn (Zea mays L. Saccharata Sturt) - I Gusti Bagus Udayana; Desak Ketut Tristiana Sukmadewi; Desak Ayu Diah Prawerti (Agriwar Journal, 2025)
This research aims to determine the effect of a combination of biological fertilizers on the growth of sweet corn plants. This research was conducted at Subak Mambal Jl. Raya Semana, Mambal Village, Abiansemal District, Badung Regency, with an altitude of 240 meters above sea level. The experiment lasted for approximately 3 months, starting from April to July 2023. This research was conducted using a single-factor Randomized Block Design (RAK), which employed five treatments with five replications, and the dose of fertilizer was calculated based on the land area. The combinations used are P1 (NPK 100%), P2 (NPK 50% + Aspergillus costaricaensis Biological Fertilizer), P3 (NPK 50% + Liquid Biological Fertilizer), P4 (Aspergillus costaricaensis Biological Fertilizer + Organic Fertilizer), P5 (Organic Fertilizer + Liquid Biological Fertilizer). The results of statistical analysis show that the combination of biological fertilizer on plant height, number of leaves, stem diameter, cob length, weight of cobs with husks, weight of cobs without husks, number of cobs, and fresh weight of roots can equalize the results from using 100% NPK even though the differences are not significant. In terms of the weight of cobs with husks and the weight of cobs without husks, the combination of 50% NPK + liquid biofertilizer can increase the weight of husked cobs and the weight of cobs without husks, which is not significantly different from the 100% NPK treatment.